2004
DOI: 10.1128/aem.70.5.2928-2934.2004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Interaction Effects of Carbon Dioxide, Sodium Chloride, and Sodium Nitrite on Neurotoxin Gene Expression in Nonproteolytic Clostridium botulinum Type B

Abstract: The effects of carbon dioxide, sodium chloride, and sodium nitrite on type B botulinum neurotoxin (BoNT/B) gene (cntB) expression in nonproteolytic Clostridium botulinum were investigated in a tryptone-peptone-yeast extract (TPY) medium. Various concentrations of these selected food preservatives were studied by using a complete factorial design in order to quantitatively study interaction effects, as well as main effects, on the following responses: lag phase duration (LPD), growth rate, relative cntB express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 28 publications
4
26
0
Order By: Relevance
“…Another approach to ensure that only live cells are detected is reverse-transcription PCR (RT-PCR), where gene expression rather than the gene itself is detected. Reverse transcription-PCR protocols for the botB and botE genes have been described (136,137,146). In a case of a human botulism outbreak, however, laborious procedures to obtain high-quality RNA may prove to be too time-consuming.…”
Section: Molecular Detection Of Clostridium Botulinummentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach to ensure that only live cells are detected is reverse-transcription PCR (RT-PCR), where gene expression rather than the gene itself is detected. Reverse transcription-PCR protocols for the botB and botE genes have been described (136,137,146). In a case of a human botulism outbreak, however, laborious procedures to obtain high-quality RNA may prove to be too time-consuming.…”
Section: Molecular Detection Of Clostridium Botulinummentioning
confidence: 99%
“…Furthermore, the requirements for selection of reagents, reaction standardization, and sample pretreatment are higher than those for conventional PCR. Quantitative detection of the botB gene has been employed for research purposes (136,137), whereas a recent application allowed the quantitative detection of C. botulinum type A spores spiked in canned corn and sausage (223) ( Table 3). In this method, DNA is extracted directly from spores and no enrichment steps are employed.…”
Section: Molecular Detection Of Clostridium Botulinummentioning
confidence: 99%
“…Interestingly, there was a hierarchy of expression signal; at all CO 2 concentrations CBO1974-1978 Ͼ CBO0123-0125 Ͼ CBO2797-2795. (5,13,15,20). Previous studies using proteolytic C. botulinum reported a delay in neurotoxin formation with headspace con- centrations in excess of 45% CO 2 (11,12,17,18), although a further report indicated that neurotoxin formation was unaffected by sparging with 100% CO 2 (30).…”
Section: Resultsmentioning
confidence: 96%
“…However, strains of nonproteolytic C. botulinum types B and E, despite having increased lag time and reduced growth rate (13,15), display an increase in both neurotoxin gene expression and neurotoxin formation with higher CO 2 concentrations (5,20). The purpose of the present study was to quantify the effect of CO 2 concentration on the growth, relative gene expression, and neurotoxin production by proteolytic C. botulinum type A1 strain ATCC 3502.…”
mentioning
confidence: 97%
“…Some researchers have reported the detection and/or quantification of C. botulinum neurotoxin genes for type A 23) , for types A, B, and E 24), 25) , for types A and B 26) , and for type E 27) . Other real-time PCR approaches, which involve quantification of RNA expression, were reported for types A and E 28) , for type B 29), 30) , and for type D 31) . These representative studies did not use duplex PCR quantification methods.…”
Section: Introductionmentioning
confidence: 99%